PENINGKATAN KEMAMPUAN PASSING DAN SMASH BOLA VOLI DENGAN MODIFIKASI ALAT BANTU DI SDN KEMAYORAN 01 BANGKALAN - Hoddin, Sholeh; Handayani, Heni Yuli; Widodo, Haryo Mukti (Fakultas Ilmu Keolahragaan Unimed, 2025)
The purpose of this study was to determine the effect of the use of assistive devices on improving volleyball passing and smashing. The type of quantitative research case study. The technique used is participant observation. The research instrument is in the form of observation sheets and documentation. The results of the study based on the results of data analysis showed that the ability of students to pass in the assessment based on the initial stage was in the